A technology package to improve growth and yield of sweet sorghum in ex-coal mining land, East Kalimantan, Indonesia - Tarbiyatul Munawwarah; Yiyi Sulaeman (Journal of Degraded and Mining Lands Management, 2023)
Huge ex-coal mining land provides the soil for crop development, yet soil improvement is required. Fertilizer and soil organic matter application and liming are standard practices to improve soil productivity. The integrated crop and land management (ICLM) package offers alternative technology to increase growth and crop yield. This study aimed to evaluate an ICLM technological package to improve sweet sorghum growth and production in the ex-coal mining land. The sweet sorghum of Bioguma 1 Agritan variety was used as the indicator crop. The ICLM was composed of mixed organic fertilizers (1,000 kg granule organic fertilizer ha-1, 10 kg Procal soil amendment ha-1, 10 kg Kayabio biofertilizer ha-1, and 5 kg NPK fertilizer    ha-1), mixed inorganic fertilizers (300 kg NPK ha-1, 50 kg Urea ha-1, 10 kg Procal soil amendment ha-1, and 10 kg Kayabio biofertilizer ha-1), and local bio-activators. The field trial used a group-randomized design with four frequencies of bio-activator application and five replications. Mixed organic fertilizer was used to cover the planting holes, where previously, the seed was soaked by a bio-activator and put into holes. The mixed fertilizer was applied to a 14-day-old plant using the hole punch method (tugal). Results of this study showed that local bio-activator significantly affected the sorghum growth and yield. The best frequency of bio-activator application was three times spraying. ICLM are prospective technology to improve soil condition, crop growth, and crop yield in ex-coal mining land.